2015
DOI: 10.1016/j.neuint.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol neuroprotection in stroke and traumatic CNS injury

Abstract: Resveratrol, a stilbene formed in many plants in response to various stressors, elicits multiple beneficial effects in vertebrates. Particularly, resveratrol was shown to have therapeutic properties in cancer, atherosclerosis and neurodegeneration. Resveratrol-induced benefits are modulated by multiple synergistic pathways that control oxidative stress, inflammation and cell death. Despite the lack of a definitive mechanism, both in vivo and in vitro studies suggest that resveratrol can induce a neuroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 147 publications
2
74
0
Order By: Relevance
“…Resveratrol is also able to increase the quantity and function of mitochondria (15). Previous studies have demonstrated that various organs, such as the liver, brain, kidney and lung, in F2 hybrid mice appear to have oxidative DNA damage with aging (12,16,17). However, the oral absorption of resveratrol may reduce the high levels of oxidative damage markers induced by aging (18).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is also able to increase the quantity and function of mitochondria (15). Previous studies have demonstrated that various organs, such as the liver, brain, kidney and lung, in F2 hybrid mice appear to have oxidative DNA damage with aging (12,16,17). However, the oral absorption of resveratrol may reduce the high levels of oxidative damage markers induced by aging (18).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all of these pathophysiologic mechanisms also mediate poststroke neuronal death (Kim and Vemuganti, 2015; Lopez et al, 2015; Nakka et al, 2016). A recent study showed that α -Syn transgenic mice are more susceptible to ischemic brain damage (Unal-Cevik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a potential drug candidate for treatment of ischemic stroke, as summarized in a recent review article [126]. Resveratrol exhibited multiprotective effects, such as antiapoptotic [127,128], antioxidative [129], anti-inflammatory [130] and antiexcitotoxic effects [131,132]. Resveratrol has a therapeutic time window up to 6 h after ischemic onset; it reduced infarct volume, attenuated microglial activation and suppressed cytokine production and free radical generation [130].…”
Section: Active Compounds From Chinese Herbal Medicine For Targeting mentioning
confidence: 99%